Perancangan Sistem Informasi Penjualan Plastik Berdasarkan Permintaan Customer - Budi Haryanto; Renaldy Agung Prasetyo; Andrianto Effendi (Jurnal Indonesia Sosial Teknologi, 2021)
CV Bina Jaya Plastik is a company engaged in the provider of promotional products in the form of clothing, stationery, bags, and premium gifts. In the business process, currently the system still uses a manual system and still has some weaknesses, one of which is the recording of goods and requests that are still recap data and stored manually using Microsoft Excell. This makes the process of buying goods and requests take a long time, and is inaccurate. Based on the analysis of Frame Work PIECES, it can be concluded that the main problem of CV Bina Jaya Plastik is the accuracy and efficiency of information that is less maximal on the running system, so with the creation of this web-based system is expected to make better information. With the design of a website-based application program at CV Bina Jaya Plastik, it is expected to help facilitate in managing data on the purchase of goods on demand and speed up the process of making reports to the leadership. Along with the progress of CV Bina Jaya Plastik which continues to grow, the information system of data on the purchase of goods on demand that runs is considered less supportive to be applied or used in CV Bina Jaya Plastic. So that the proposed system is expected to facilitate and speed up processing and obtain accurate information from the processing of goods purchase data on demand.